Annona Squamosa Leaf Extract as an Efficient Bioreducing Agent in the Synthesis of Chromium and Nickel Nanoparticles - Mamuru, Solomon A.; Bello, Abubakar S.; Hamman, Saminu B. (International Journal of Applied Sciences and Biotechnology, 2015)
Biosynthesis is one of the rapid, reliable, and eco-friendly routes for the synthesis of metal nanoparticles in areas of nanotechnology research. The synthesis of chromium and nickel nanoparticles using Annona squamosa leaf extracts at neutral pH was studied. The formed metal nanoparticles were confirmed by colour changes from colourless to dark brown and it was characterized using UV-visible and Fourier transform infrared spectroscopy. UV-visible spectrums of the aqueous medium containing the metal nanoparticles show a surface Plasmon resonance at 285 nm. FT-IR analysis reveals that phytochemical groups of aromatic amine character might be responsible for the reduction to metal nanoparticles. Int J Appl Sci Biotechnol, Vol 3(2): 167-169 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.11651